Differences in the Composition of Vaginal Microbiota between Women Exhibiting Spleen-Deficiency Syndrome and Women with Damp-Heat Syndrome, Two of the Most Common Syndromes of Vaginitis in Traditional Chinese Medicine. (24th October 2019) - Lin, Wei Xian; Du, Xin; Yang, Li Lin; Chen, Si Yun; Qiu, Wei Yu; Wu, Hai Wang; Zhao, Guang; Feng, Yi Hui; Yu, Qing Ying; Tian, He; Luo, Song ping; Gao, Jie
Abstract : Spleen-deficiency syndrome and damp-heat syndrome are the two most common syndromes of vaginitis in traditional Chinese medicine (TCM). Although it is known that the vaginal microbiota is closely associated with vaginitis, present studies have not fully elucidated the relationship between the composition of the vaginal microbiome and type of TCM syndrome because of the limitations in the present reductionist approaches. Samples of vaginal secretions were collected from patients with bacterial vaginitis and healthy subjects with spleen-deficiency syndrome and damp-heat syndrome, in order to analyze the constitution of the vaginal microflora using 16S rRNA sequencing methods that encompass taxonomic units, alpha diversity rarefaction curves, and principal component analyses. This prospective study indicated that there was a statistically significant difference in the composition of the vaginal microbiome between patients with spleen-deficiency syndrome and patients with damp-heat syndrome. Streptococcus was the dominant microbiota in patients with spleen-deficiency syndrome. This can serve as a biomarker for differentiating spleen-deficiency syndrome and damp-heat syndrome. In addition, as indicated by the findings on the samples, patients with bacterial vaginitis of dominant abundance in Pseudomonadaceae might be prone to manifest spleen-deficiency syndrome, while patients with bacterial vaginitis of dominant abundance in Prevotella might be prone to manifest damp-heat syndrome. These present findings can provide a new approach to acquire a scientific understanding of the syndromes of TCM, which in turn would benefit the development of personalized medicine, in terms of ancient medicine and complex biological systems.